The Influence of Social Media Influencers on Consumers' Buying Attitudes and Intentions - Mutiara Rifki Azkiah; Arif Hartono (CV. Lenggogeni Data Publishing, 2023)
This study examines the influence of social media influencers on attitudes and purchase intentions of consumers in Indonesia. In the era of the industrial revolution 4.0, digital marketing strategies and the use of social media are important for business people. One form of strategy that is currently trending among industry players is the use of social media influencers. This study aims to examine the extent to which social media influencers influence consumer attitudes and purchase intentions in Indonesia. This study used a quantitative approach and data was collected from 180 respondents who are active users of social media and have followed social media influencer accounts. The results of the study show that social media influencers have a positive and significant influence on consumer attitudes and purchase intentions. These findings contribute to business people in determining marketing strategies and using social media influencers as social relations assets that can help improve product branding, build community, and develop loyalty. This research also provides insights for researchers and marketing practitioners regarding the importance of understanding the role of social media influencers in influencing consumer behavior in the digital era.